One to many (new scheme for symmetric cryptography) - Alz Danny Wowor; Bambang Susanto (Universitas Ahmad Dahlan, 2023)
Symmetric cryptography will always produce the same ciphertext if the plaintext and the given key are the same repeatedly. This condition will make it easier for cryptanalysts to perform cryptanalysis. This research introduces a one-to-many cryptography scheme, which can produce different ciphertexts even if the input given is the same repeatedly. The one-to-many encryption scheme can produce several ciphertexts with differences of up to 50%. The avalanche effect test obtained an average of 52.20%, better than modern cryptography Blowfish by 25.46% and 6% better than advanced encryption standard (AES). One-to-many can produce different n-ciphertexts, which will certainly make it more difficult for cryptanalysts to perform cryptanalysis and require n-times longer to break than other symmetric cryptography.